After Queer Theory - Penney, James (Pluto Press, 2014)
After Queer Theory makes the provocative claim that queer theory has run its course, made obsolete by the elaboration of its own logic within capitalism. James Penney argues that far from signalling the end of anti-homophobic criticism, however, the end of queer presents the occasion to rethink the relation between sexuality and politics.Through a critical return to Marxism and psychoanalysis (Freud and Lacan), Penney insists that the way to implant sexuality in the field of political antagonism is paradoxically to abandon the exhausted premise of a politicised sexuality.After Queer Theory argues that it is necessary to wrest sexuality from the dead end of identity politics, opening it up to a universal emancipatory struggle beyond the reach of capitalism's powers of commodification.
The Limits of Sexual Politics
Keywords: Queer Theory; Sexualität; Politik; Identität; 300 Sozialwissenschaften